Combined targeting of AKT and mTOR synergistically inhibits proliferation of hepatocellular carcinoma cells - Grabinski, Nicole (BioMed Central, 2012)
BACKGROUND: Due to the frequent dysregulation of the PI3K/AKT/mTOR signaling pathway, mTOR represents a suitable therapeutic target in hepatocellular carcinoma (HCC). However, emerging data from clinical trials of HCC patients indicate that mTOR inhibition by RAD001 (Everolimus) alone has only moderate antitumor efficacy which may be due to the feedback activation of AKT after mTOR inhibition. In this study, we analyzed the effects of dual inhibition of mTOR and AKT on the proliferation of HCC cell lines. In addition, we measured the feedback activation of each of the AKT isoforms after mTOR inhibition in HCC cell lines and their enzymatic activity in primary samples from HCC patients. METHODS: The activation status of specific AKT isoforms in human HCC samples and corresponding healthy liver tissue was analyzed using an AKT isoform specific in vitro kinase assay. AKT isoform activation after mTOR inhibition was analyzed in three HCC cell lines (Hep3B, HepG2 and Huh7), and the impact of AKT signaling on proliferation after mTOR inhibition was investigated using the novel AKT inhibitor MK-2206 and AKT isoform specific knockdown cells. RESULTS: AKT isoforms become differentially activated during feedback activation following RAD001 treatment. The combination of mTOR inhibition and AKT isoform knockdown showed only a weak synergistic effect on proliferation of HCC cell lines. However, the combinatorial treatment with RAD001 and the pan AKT inhibitor MK-2206 resulted in a strong synergism, both in vitro and in vivo. Moreover, by analyzing primary HCC tissue samples we were able to demonstrate that a hotspot mutation (H1047R) of PI3KCA, the gene encoding the catalytic subunit of PI3K, was associated with increased in vitro kinase activity of all AKT isoforms in comparison to healthy liver tissue of the patient. CONCLUSION: Our results demonstrate that dual targeting of mTOR and AKT by use of RAD001 and the pan AKT inhibitor MK-2206 does effectively inhibit proliferation of HCC cell lines. These data suggest that combined treatment with RAD001 and MK-2206 may be a promising therapy approach in the treatment of hepatocellular carcinoma.